Infrasound recordings from an array of microbarometers onboard three stratospheric balloons launched from Esrange Space Center, Kiruna, Sweden, on August 20, 2020 ... : Infraljudregistreringar från en uppsättning mikrobarometrar ombord på tre stratosfärsballonger släppta från Esrange Space Center, Kiruna, Sverige, den 20:e augusti, 2020 ... - Kero, Johan; Bowman, Daniel; Bird, Eli; Lees, Jonathan (Swedish Institute of Space Physics, 2022)
Three balloons (B1-B3) were launched from ESRANGE Space Center (67.89 N, 21.08 E) on August 20, 2020. The balloons were designed to carry two payload boxes, separated by a 100 meter tether. Each payload box contained a DiGOS DATA-CUBE, recording three InfraBSU infrasound microbarometers at 400 Hz. One microbarometer recorded true polarity of acoustic signals, another recorded reversed polarity, and flow filters covered both ports on the final microphone, preventing acoustic waves from registering on the device. This data set contains a combination of data from the first and second microphones. In subtracting the polarity-reversed data from the true-polarity data, we expect acoustic signals to remain intact and non acoustic noise sources (e. g. electromagnetic interference, vibration) to be removed from the data. ... : Infraljudregistreringar från en uppsättning mikrobarometrar ombord på tre stratosfärsballonger släppta från Esrange Space Center, Kiruna, Sverige, den 20:e augusti, 2020. För fler detaljer, se beskrivning på engelska. ...